2013
DOI: 10.1002/ejic.201300511
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Coordination Behaviour of 3,5‐Di(2‐pyridyl)‐1,2,4‐oxadiazole

Abstract: The coordination behaviour of 3,5-di(2-pyridyl)-1,2,4-oxadiazole (LЈ) has been studied and compared with that of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Here, investigations on the coordination behavior of 3-(6-methyl-2-pyridyl)-[1,2,4]triazolo[4,3- a ]pyridine ( L , Figure b), a derivative of L 1 featuring an additional methyl group in the 6-position of the pyridine substituent, are presented. This feature is expected to impose sterical stress on the coordination sphere of the resulting transition metal complexes and therefore hinder the formation of 2:1-type complexes with a trans -( N ′, N 1 ) 2 coordination, like the ones L 1 and other similar 2-pyridyl-substituted azole-ligands tend to form.…”
Section: Introductionmentioning
confidence: 99%
“…Here, investigations on the coordination behavior of 3-(6-methyl-2-pyridyl)-[1,2,4]triazolo[4,3- a ]pyridine ( L , Figure b), a derivative of L 1 featuring an additional methyl group in the 6-position of the pyridine substituent, are presented. This feature is expected to impose sterical stress on the coordination sphere of the resulting transition metal complexes and therefore hinder the formation of 2:1-type complexes with a trans -( N ′, N 1 ) 2 coordination, like the ones L 1 and other similar 2-pyridyl-substituted azole-ligands tend to form.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many 1,2,4-oxadiazole derivate structures have been detected using X-ray structure spectroscopy (1-4) [26,27]. The structures that can be used in energetic materials [28] and complex compounds based on 1,2,4-oxadiazole derivatives that can bind copper or cobalt cations, and have biological activity, have been determined [29][30][31] (Figure 4). Due to the realtively low aromaticity and high susceptibility of the O-N bond to reduction, 1,2,4-oxadiazoles are investigated for the possibility of rearrangement into other heterocyclic compounds.…”
Section: Chemistry Of Oxadiazolesmentioning
confidence: 99%
“…Over the last few decades several research studies have shown the importance of transition metal complexes in various fields such as biology for their antibacterial [1,2], antifungal [1,3] or antitumor [4,5] activities; pharmacology for the treatment of certain diseases [6,7] and catalysis for the selectivity of reactions [8,9]. Since the nitrogen atom is present in many natural molecules or in those of pharmacological interest [6,10], research has been devoted to the synthesis of transition metal complexes with hetero-atom and chelating ligands [11][12][13]. It is also well established that some of these organic molecules (drugs) are much more effective when administered linked to a metal [14][15][16].…”
Section: Introductionmentioning
confidence: 99%